2020
DOI: 10.3389/fcimb.2020.00042
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Changes in Transcriptomic “Fingerprints” and Immunological Cells in the Large Organs of Patients Dying of Acute Septic Shock and Multiple Organ Failure Caused by Neisseria meningitidis

Abstract: Background: Patients developing meningococcal septic shock reveal levels of Neisseria meningitidis (10 6-10 8 /mL) and endotoxin (10 1-10 3 EU/mL) in the circulation and organs, leading to acute cardiovascular, pulmonary and renal failure, coagulopathy and a high case fatality rate within 24 h. Objective: To investigate transcriptional profiles in heart, lungs, kidneys, liver, and spleen and immunostain key inflammatory cells and proteins in post mortem formalin-fixed, paraffin-embedded (FFPE) tissue samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 161 publications
(211 reference statements)
2
35
0
3
Order By: Relevance
“…S3E). 37 In summary, this in vitro and in vivo evidence showed that hepatocytes recruited RMs to the liver via CCL2-mediated pathways during endotoxemia.…”
Section: Validation Of Hepatocyte Recruitment Of Macrophages Via a Cc...mentioning
confidence: 63%
“…S3E). 37 In summary, this in vitro and in vivo evidence showed that hepatocytes recruited RMs to the liver via CCL2-mediated pathways during endotoxemia.…”
Section: Validation Of Hepatocyte Recruitment Of Macrophages Via a Cc...mentioning
confidence: 63%
“…Here we propose an essential role for the highly conserved Ppp1r15a uORF in the outcomes of sepsis-induced kidney injury. Sepsis is a complex pathological state where multiple pathways are aberrantly activated [45][46][47][48][49][50] . While these changes are spatially and temporally diverse, one major driver that underlies this dynamic state is the activation of antiviral responses.…”
Section: Discussionmentioning
confidence: 99%
“…Необходимо отметить, что септический шок, вызванный Neisseria meningitidis, является наиболее тяжелым из-за быстрой прогрессии клинических симптомов и раннего развития полиорганной недостаточности [12,20]. Для такого септического шока характерен наиболее выраженный дисбаланс между свертывающей и фибринолитической системами крови.…”
Section: патофизиология септического шокаunclassified
“…Микротромбоз и эндотелиальная дисфункция, связанные с провоспалительным ответом, снижают эндотелиальную экспрессию тромбомодулина и рецепторов эндотелиального протеина С, тем самым снижая и фибринолиз. Прокоагулянтное и провоспалительное состояние, связанное с этими изменениями, вызывает эндоваскулярное повреждение, микроваскулярный тромбоз, ишемию органов и в конечном итоге -полиорганную недостаточность [12]. Результаты исследования B.S.…”
Section: патофизиология септического шокаunclassified
See 1 more Smart Citation